Old Battlefields And Their Lessons: The Case Of Antietam - Votaw, John (Teaching History: A Journal of Methods, 1996)
A drive by Gettysburg, Pennsylvania, on a warm summer day will convince you that many people think of old battlefields as a vacation destination. These same places, however, are excellent outdoor classrooms to teach and learn about history. In the United States Civil War battlefields were preserved intentionally as places to instruct officers of the militia and regular army, as well as to honor those who fought and fell there. The U.S. Army began to place interpretive markers on several battlefields more than a century ago and army officers still visit those same battlefields today to study military history. Today’s military visitor prepares for a close examination of a Civil War battlefield using an old educational technique called the staff ride.